2023
DOI: 10.15360/1813-9779-2023-1-2202
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Pathogenesis of Postoperative Cognitive Dysfunction (Review)

Abstract: Impairment of higher mental functions can complicate the course of the postoperative period even after short and minimally invasive, including laparoscopic, surgical procedures. Postoperative cognitive dysfunction significantly challenges patients’ quality of life, negating real success of surgical intervention and anesthetic support. In some cases, early postoperative cognitive dysfunction may be one of the main predictors of persistent cognitive impairment.The purpose of the review. To contemplate etiology, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
(48 reference statements)
0
0
0
Order By: Relevance
“…The first signs of POCD can appear hours after a surgical procedure and even persist for months. POCD is characterized as a decline in cognitive function, and the Medicina 2023, 59, 2034 2 of 9 manifestation range includes impaired memory, speech, and reasoning, as well as difficulty concentrating, and POCD has associated with a prolonged time before returning to work, early retirement, and a rise in mortality rates [1]. The diagnosis of POCD is mainly based on subjective neuropsychological testing tools [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first signs of POCD can appear hours after a surgical procedure and even persist for months. POCD is characterized as a decline in cognitive function, and the Medicina 2023, 59, 2034 2 of 9 manifestation range includes impaired memory, speech, and reasoning, as well as difficulty concentrating, and POCD has associated with a prolonged time before returning to work, early retirement, and a rise in mortality rates [1]. The diagnosis of POCD is mainly based on subjective neuropsychological testing tools [2].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that by blocking the sympathetic system's overactivation, postoperative cognition can be significantly improved [9]. Intraoperative awakening could also negatively contribute to the patient's postoperative condition [1].…”
Section: Introductionmentioning
confidence: 99%